Analysis of the Prevalence of Polycystic Ovarian Syndrome and its Association with Clinical Criteria in Adolescent Girls from Rural Areas - Mundada, Atulkumar (Journal of Biomedical and Pharmaceutical Research, 2015)
Background: Polycystic Ovarian Syndrome (PCOS) is a common endocrine disorder affecting adolescent girls and women of reproductive age. The prevalence and clinical presentation of PCOS can vary significantly across different populations. Rural areas often face unique challenges in healthcare delivery, which can impact the diagnosis and management of PCOS. This study aims to analyze the prevalence of PCOS and its association with clinical and biochemical criteria among adolescent girls from rural areas. Developing healthcare infrastructure that integrates PCOS management into routine adolescent health services can improve outcomes. The findings highlight the need for better healthcare access in rural areas. This includes training healthcare providers to recognize and manage PCOS effectively and ensuring that diagnostic and treatment facilities are available. Cultural norms and misconceptions may impact the diagnosis and management of PCOS in rural populations. Tailoring healthcare interventions to address these cultural barriers and involving community leaders in health promotion activities can enhance the acceptance and effectiveness of PCOS management programs. Aim: The aim of this study is to investigate the prevalence of Polycystic Ovarian Syndrome (PCOS) among adolescent girls residing in rural areas and to analyze its association with clinical and biochemical criteria. Material and Method: A cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Tertiary care Hospital. A total of 100 adolescent girls aged 12-19 years from selected rural areas were initially invited based on inclusion and exclusion criteria. Out of these, 80 girls voluntarily participated in the study. Participants underwent a comprehensive assessment, including clinical examinations, biochemical blood tests, and ultrasound examinations. Clinical criteria for PCOS included menstrual irregularities, signs of hyperandrogenism, and polycystic ovaries. Biochemical criteria assessed included hormonal levels (LH, FSH, free testosterone) and markers of insulin resistance (insulin levels, HOMA-IR). Data were analyzed to determine the prevalence of PCOS and the relationship between clinical symptoms and biochemical markers. Results: The study found that the prevalence of PCOS among adolescent girls in rural areas was 25%. Girls with PCOS presented with a higher incidence of menstrual irregularities and symptoms of hyperandrogenism, including acne and hirsutism, compared to those without PCOS. Biochemical analysis revealed significantly higher levels of Luteinizing Hormone (LH) and free testosterone in the PCOS group. Insulin resistance, as indicated by elevated insulin levels and HOMA-IR values, was also more pronounced in PCOS patients. The LH ratio did not show significant differences between the two groups. Thyroid function tests indicated slightly elevated TSH levels in the PCOS group, though differences in T3 and T4 levels were not substantial. Conclusion: PCOS is prevalent among adolescent girls in rural areas, with clinical and biochemical characteristics aligning with those found in other populations. The higher prevalence of menstrual irregularities, hyperandrogenism, and insulin resistance in rural adolescents with PCOS highlights the need for targeted healthcare interventions. Improved access to healthcare services and educational programs tailored to rural settings can enhance early diagnosis and management of PCOS. Further research is needed to explore long-term outcomes and additional factors contributing to PCOS in rural populations. Keywords: Polycystic Ovarian Syndrome, PCOS, Prevalence, Adolescent Girls, Rural Areas, Clinical